ANALISIS KECELAKAAN LALU LINTAS PADA RUAS JALAN KINALI-SIMPANG EMPAT PASAMAN BARAT - Daniati, Sisra; Kurniawan, Deddy; Bastian, Elfani (Jurnal Riset Multidisiplin Agrisosco, 2023)
The Kinali-Simpang Empat road in Kabupaten Pasaman Barat has a fairly high accident rate with a length   23 Km and an effective width of   7 m. This analysis is used to determine the characteristic of accidents and the factors that cause traffic accident. The method used in this analysis is the AEK (Accident Equivalent Rate) method and the correlation test using SPSS. Based on the results of the analysis, there is the highest number of each characteristic namely based on the type of victim as many as 91 victims with minor injuries category, based on the day 41 cases that occurred on Sunday, based on the time of the incident 141 cases of accidents that occurred at 06.00 – 19.00, based on the type of vehicle involved 169 cases with the type of motorcycle vehicle, based on the age of the suspect and victim 83 cases with an age range of 16-30 years, based on the type of accident what happened 71 cases with front-to-front collision type accident, based on the location of the accident 59 cases with locations in Rimbo Tampoeroeng, and for the main factor causing the accident 104 cases with the drive category. Efforts to prevent traffic accident are to provide traffic education and strict sanctions on road user who violate traffic regulations.